MEDAN MAKNA VERBA MEMASAK DALAM BAHASA MELAYU DIALEK KETAPANG - Norvadilah, Wiwin; Saman, Sisilya; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstrak: Penelitian ini dilatarbelakangi oleh adanya keberagaman medan makna verba memasak dalam Bahasa Melayu Dialek Ketapang. Penelitian ini bertujuan mendeskripsikan verba memasak dalam Bahasa Melayu Dialek Ketapang. Masalah umum dalam penelitian ini adalah â€œBagaimanakah medan makna verba memasak dalam Bahasa Melayu Dialek Ketapang?â€. Penelitian ini menggunakan metode lingustik deskriptif dengan bentuk Â kualitatif. Berdasarkan hasil analisis data ditemukan Berdasarkan hasil analisis data terdapat 27 leksem verba memasak dalam Bahasa Melayu Dialek Ketapang yang dianalisis dari 7 sudut pandang. Jenis makna verba memasak dalam Bahasa Melayu Dialek Ketapang diperoleh 27 makna leksikal, 22 makna gramatikal, dan 21 makna referensial, 27 makna denotatif, 1 makna kata, 4 makna kolokatif. Fungsi semantis dari leksem-leksem pada medan makna verba memasak dalam Bahasa Melayu Dialek Ketapang adalah untuk memasak baik yang menggunakan media air, minyak ataupun tidak menggunakan minyak dan air. Â  Kata kunci: medan makna, verba memasak, Bahasa Melayu Dialek Ketapang Abstract: The backgroundÂ  of this research is various semantic domain of cooking verb in Melayu Ketapang Dialect. This research purposes the describe about cooking verb in Melayu Ketapang Dialect. General problem in this research is â€œHow semantic domain of cooking verb in Melayu Ketapang Dialect?. This research uses linguistic descriptive method with qualitative form. Based on data analysis result there are 27 lexemes of cooking verb in Melayu ketapang Dialect which is analysed from 7 viewpoint. The type meaning of cooking verb in Melayu Ketapang Dialect are obtained 27 lexical meanings, 22 grammatical meanings, 21 referential meanings, 27 denotasional meanings, 1 word meaning, and 4 kolokatif meanings. Semantic functions of lexem in semantic domain of cooking verb in Melayu Ketapang Dialect are to cook both used water, oil and fire (not using oil and water). Â  Keywords: semantic domain, cooking verb, Melayu Ketapang Dialect.